The logic of appropriateness: with the introduction of Bob Jessop - March, James G.; Olsen, Johan P. (Journal of Public Governance, 2014)
The logic of appropriateness is a perspective that sees human action as driven by rules of appropriate or exemplary behavior, organized into institutions. Rules are followed because they are seen as natural, rightful, expected, and legitimate. Actors seek to fulfill the obligations encapsulated in a role, an identity, a membership in a political community or group, and the ethos, practices and expectations of its institutions. Embedded in a social collectivity, they do what they see as appropriate for themselves in a specific type of situation. The paper is divided into five parts. First, we sketch the basic ideas of rule-based action. Second, we describe some characteristics of contemporary democratic settings. Third, we attend to the relations between rules and action, the elements of slippage in executing rules. Fourth, we examine the dynamics of rules and standards of appropriateness. And, fifth, we discuss a possible reconciliation of different logics of action, as part of a future research agenda for students of democratic politics and policy making.